Penguatan Literasi Keuangan Dalam Pengembangan Umkm Di Desa Matotonan Kecamatan Siberut Selatan Kabupaten Mentawai - Gustia Harini; Syailendra Eka Saputra; Wati Wati; Yesmira Syamra; Indra Mulia Pratama (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The success of a business development cannot be separated from the ability of each individual who manages the business to utilize all the potential resources they have, both the quality of human resources and financial resources in developing a business. When resource management has been carried out, it is very important to record accounting-based financial transactions to find out the amount of capital and finance that has been obtained, so that through reporting compiled in a financial report, various policy strategies can be developed that can be further developed. especially micro enterprises in the community in Mototonan Village, which is located in the District of South Siberut, Mentawai Regency.